A review of reproductive biotechnologies and their application in goat - Abdullah, Ramli; Khadijah, W.E.W.; Rahman, A.N.M.A. (2008)
Tremendous developments have been achieved in the field of assisted reproductive technology (ART) both in human and animals in the last two decades. In livestock including goats, the modern ARTs are being used for the improvement and preservation of livestock genetics and the enhancement of reproductive efficiency. The ARTs together with embryo technologies have facilitated the development of methods to transfer desired single genes or the entire genome from desirable individuals or embryos. Rapid advances in ARTs to manipulate embryos in the laboratory have permitted screening of embryos for genetic defects or highly desirable quantitative traits using molecular markers. The ARTs include artificial insemination, embryo transfer, estrus synchronization and superovulation, multiple ovulation embryo transfer, laparoscopic ovum pick-up, in vitro production of embryos, intracytoplasmic sperm injection, cryopreservation of sperm, cryopreservation of oocytes and embryos, sexing of sperm and embryos, embryo splitting, cloning and gene transfer and marker-assisted selection. The goat is an excellent model for all these ARTs and has been used extensively in both basic and applied research. The applications of these ARTs in goat enable to increase the rate of genetic progress, reduce generation interval, enhance production, help utilizing genetically important but biologically inferior individual, improve the management of infertile/sub-fertile buck/doe and eliminate reproductive diseases. This review describes different ARTs and their application in goat production and research. © 2008 Asian Network for Scientific Information.